WACANA PEMIMPIN PEREMPUAN DALAM ISLAM - Meyzarti Yazid (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper discusses women's leadership in Islam. There are three spheres of leadership that are the focus of the study: women leaders in the domestic sphere, women leaders in the public sphere, and women leaders within the scope of worship. These three spheres are studied separately because they have different epistemological contexts and foundations. Through the normative approach and analysis of several legal propositions concluded that the discourse of leadership in the family and the scope of worship is more dominantly owned by men than women. The dominance of male leadership in this context is more due to the normative religious epistemological foundations and some laws that place men as heads of families. Women's leadership in worship is permitted within certain limits and conditions. Different in the context of leadership in the public sphere, women's leadership discourse has been able to place the same position with men even if in some circles rejects women's leadership.